Association of Thromboembolic Risk Score with Left Atrial Thrombus and Spontaneous Echocardiographic Contrast in Non-Anticoagulated Nonvalvular Atrial Fibrillation Patients - Huang, Jun; Liao, Hong-Tao; Fei, Hong-Wen; Xue, Yu-Mei; Zhang, Li; Lin, Qiong-Wen; Ren, Si-Qi; Zhan, Xian-Zhang; Fang, Xian-Hong; Zheng, Mu-Rui; Wu, Shu-Lin; Xu, Lin (Cardiology, 2018)
The aim of the study was to examine the association of CHADS2/CHA2DS2-VASc scores with left atrial thrombus (LAT) and spontaneous echocardiographic contrast (SEC) in non-anticoagulated nonvalvular atrial fibrillation (NVAF) spontaneous patients, and to develop a new scoring system for LAT/SEC prediction. Consecutive non-anticoagulated NVAF patients with or without LAT/SEC by transesophageal echocardiography were identified in the Guangdong General Hospital. Among 2,173 patients, the prevalence of LAT/SEC was 4.9%. Both predictive values of CHADS2 and CHA2DS2-VASc scores for the presence of LAT/SEC were low-to-moderate (receiver operating characteristic [ROC] = 0.591 and 0.608, respectively, p = 0.90). By multivariate analysis, non-paroxysmal AF, decreased left ventricular ejection fraction, and left atrial enlargement were positively associated with LAT/SEC, while CHADS2/CHA2DS2VASc scores were not. A new scoring system based on these 3 factors above significantly improved the discrimination for LAT/SEC (ROC = 0.792). CHADS2/CHA2DS2-VASc scores had limited value in predicting LAT/SEC; a new scoring system that combines AF type and echocardiographic parameters may better predict LAT/SEC as a surrogate for cardioembolic risk in NVAF patients.